Insight into the biochemical and physiological mechanisms of nanoparticles-induced arsenic tolerance in bamboo - Emamverdian, Abolghassem; Ding, Yulong; Hasanuzzaman, Mirza; Barker, James; Liu, Guohua; Li, Yang; Mokhberdoran, Farzad (Frontiers in Plant Science, 2023)
Introduction Arsenic (As) contamination in soil, sediments, and water poses a significant threat to the growth of bamboo plants. However, nanoparticles with high metal absorbance capacity can play a key role in the reduction of heavy metals toxicity in plants as well as maintaining their growth under toxicity. Methods Hence, an in vitro experiment was conducted to determine the influence of three types of nanoparticles: 150 µM silicon nanoparticles (SiO2 NPs), 150 µM titanium nanoparticles (TiO2 NPs), and 150 µM zinc oxide nanoparticles (ZnO NPs) on As (150 µM and 250 µM) tolerance enhancement of a one-year-old bamboo species (Pleioblastus pygmaeus). Results and discussion The results showed that while As at 150 µM and 250 µM significantly disrupted the plant growth by excessive generation of reactive oxygen species (ROS) components, and inducing cell membrane peroxidation, the addition of NPs increased both enzymatic and non-enzymatic antioxidant activities, upregulated glyoxalase defense system, and improved gas exchange parameters and photosynthetic pigments content, leading to the enhanced plant shoot and root dry weight. These were achieved by lowering levels of ROS, electrolyte leakage (EL), malondialdehyde (MDA), hydrogen peroxide (H2O2) and the superoxide radical (O2•−), as well as decreasing As accumulation in the plant organs. Thus, it might be concluded that ZnO NPs, SiO2NPs, and TiO2NPS alone or in combination can significantly increase the bamboo plant tolerance to As toxicity via key mechanisms, including induction of various antioxidants and glyoxalase defense systems, scavenging of ROS and methylglyoxal (MG), increasing phytochelatins production, reduction of As accumulation and translocation, and improving photosynthetic pigments under As toxicity. Additionally, the results showed that the combined application of 150 µM ZnO NPs, SiO2 NPs, and TiO2 NPs had the greatest effect on enhancing the plant tolerance to As at 150 µM and 250 µM.